THE FORMATION OF A GREEN ECONOMY IN UZBEKISTAN AS THE FOUNDATION FOR ACHIEVING DEVELOPMENT GOALS (World Economics and Finance Bulletin, 2025)
The article emphasizes the importance of shifting Uzbekistan's economic activities towards minimizing environmental risks. It highlights that the transition to a "green economy" is not just a new model, but a strategically important step for ensuring the country's sustainable development. This economic model aims to improve the quality of life for the population, create conditions for long-term well-being, and protect the interests of future generations. Special attention is given to the implementation of environmentally safe technologies during the transition, which not only contributes to environmental protection but also improves social conditions and ensures justice for all segments of society in Uzbekistan.
Keywords: green economy; sustainable development; environmental sustainability